Kedudukan Anak Sumbang Dalam Penerimaan Hak Nafkah Hidup Ditinjau Dalam Perspektif Hukum Islam - Mardatilla Harza Tomaluhu; La Ode Angga; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Discordant children or children resulting from blood staining are children born from the relationship of a man and a woman where both of them are prohibited from marrying because they are bound by blood relations, marital relations or breastfeeding relationships.Purposes of the Research: This study aims to explain and inform about the status and position of the discordant child as well as the protection of the living rights of the donor child according to Islamic law. Methods of the Research: This study uses normative legal research methods, and the collection of legal materials is carried out by literature study, then analyzed by qualitative means.Results of the Research: Discordant children or children resulting from blood staining are children born from the relationship of a man and a woman where both of them are prohibited from marrying because they are bound by blood relations, marital relations or breastfeeding relationships. Article 186 of the Compilation of Islamic Law does not provide protection for the rights of discordant children which are given to children resulting from adultery.